Proceedings of the 2nd Sari Mulia International Conference on Health and Sciences 2017 (SMICHS 2017) 2017
DOI: 10.2991/smichs-17.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Diabetes Self Management Education On Stress Level Of Diabetes Mellitus Patient In Area Puskesmas Cempaka Banjarmasin

Abstract: Objective : To analyze the effect of DSME (Diabetes Self Management Education) on stress level of Diabetes Mellitus patient in area of Cempaka Public Health Center (Puskesmas) Banjarmasin. Method : This study used pre-experimental design with one group pretest-posttest design. The sample used 15 people who live in area of Cempaka Public Health Center Banjarmasin. Data was analyzed using Wilcoxon test with a confidence level of 95%. Results : Result showed a difference stress level in Diabetes Mellitus patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The results of the study reported that most patients with type 2 diabetes mellitus experienced moderate stress [11][12][13]. Another study also found that half of patients with type 2 diabetes mellitus experienced moderate stress [14,15]. Stress that occurs in type 2 DM patients will cause advanced conditions or complications.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study reported that most patients with type 2 diabetes mellitus experienced moderate stress [11][12][13]. Another study also found that half of patients with type 2 diabetes mellitus experienced moderate stress [14,15]. Stress that occurs in type 2 DM patients will cause advanced conditions or complications.…”
Section: Introductionmentioning
confidence: 99%
“…This condition has a mild to severe spectrum, and in addition to physical complications, it causes mental disorders. In this regard, diagnostic methods and strict treatment and healthcare plans can contribute to diabetes distress (6).…”
Section: Introductionmentioning
confidence: 99%
“…The results of Mahdiyah and Rifka showed that diabetic patients developed diabetes distress due to fear of complications of diabetes, changes in lifestyle/economic status, and long-term treatment. In this respect, self-care education has been reported to reduce the complications of diabetes and improve the quality of life (6). Several studies have shown that inadequate self-care in diabetes accounts for emotional and behavioral stress and that fear of diabetes complications as a major stressor and cause of diabetes distress affects health and reduces quality of life (8).…”
Section: Introductionmentioning
confidence: 99%